Investment Strategies for Strengthening the Organizational Knowledge System in Industrial Business Entities - Margarita Ekadjaja; Rorlen Rorlen (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
Companies in the industrial sector can continue to advance on the challenging path of innovation and trade competitiveness in this era of knowledge management. This study aims to discuss effective investment strategies that will be implemented in building organizational knowledge systems in Indonesian industrial commercial entities. This study uses literature analysis and secondary data focusing primarily on three critical areas: innovation and research, employee education and training, and Information and Communication Technology (ICT). The Organizational Knowledge Index is used as a measure of the effectiveness of Miami's knowledge system, over the period 2019-2024. The findings indicate that investment in R&D and innovation has the greatest impact on strengthening communicative organizational knowledge systems. This covers 47.2% of the total, with ICT in second place at 32.5%, followed by staff training at 20.3%. Less dichotomous are companies that find a balance between the three investment items. Their operational efficiency, ability to innovate, and competitiveness are seen to improve significantly. The results also show that when technology investment and human resource capacity development are combined, this plays a significant role in strengthening organizational knowledge systems. This study offers empirical evidence for designing investment strategies tailored to knowledge management objectives.